MILICJA OBYWATELSKA W POWIECIE ZIELONOGÓRSKIM W LATACH 1945-1950 - Piotr Krystians (In Gremium. Studies in History, Culture and Politics, 2010)
CIVIC MILITIA IN THE POVIAT OF ZIELONA GÓRA IN THE YEARS 1945-l950The years 1945-1950 were the period of creation and devełopment of the organisational and personal foundations as well as the development of activity methods of Civic Militia-a formation which constituted one pillar of the post-war force apparatus and which became the guard of the communist parry's affairs (PPR- Polish Workers' Party l PZPR- Polish United Workers' Party).Systemic solution introduced at that time (Civic Miłitia's subordination to the safety apparatus) caused that apart from fulfilling basic tasks connected with prosecution of crimes and ensuring public order, the Civic Militia was included in the process of social, political and economic changes implemented by the communist authority.Civic Militia's entities organised in the poviat of Zielona Góra in June 1945, from the very beginning had to struggle with numerous problems and shortcomings in the following areas: personnel policy (offenses and discipline breach performed by Civil Militia's officers), efficient training process, proper equipment and working conditions (means of transport, uniforms, salaries) all of which inevitably influenced the effectiveness of activities undertaken by this formation. Apart from fulfilling tasks aiming at detecting criminals and undertaking preventive measures, Civic Militia's entities in the poviat of Zielona Góra were used, in a lesser degree than entities in other regions, in repressive activities initiated by the authorities in the social and political fields (fight with the armed underground forces, political opposition suppression, repressions towards the Church) and economic sphere (fight with speculation, the countryside collectivisation).